ARHGDIA: a novel gene implicated in nephrotic syndrome. Issue 5 (22nd February 2013) - Gupta, Indra Rani; Baldwin, Cindy; Auguste, David; Ha, Kevin C H; El Andalousi, Jasmine; Fahiminiya, Somayyeh; Bitzan, Martin; Bernard, Chantal; Akbari, Mohammad Reza; Narod, Steven A; Rosenblatt, David S; Majewski, Jacek; et al.
Abstract : Background: Congenital nephrotic syndrome arises from a defect in the glomerular filtration barrier that permits the unrestricted passage of protein across the barrier, resulting in proteinuria, hypoalbuminaemia, and severe oedema. While most cases are due to mutations in one of five genes, in up to 15% of cases, a genetic cause is not identified. We investigated two sisters with a presumed recessive form of congenital nephrotic syndrome. Methods and results: Whole exome sequencing identified five genes with diallelic mutations that were shared by the sisters, and Sanger sequencing revealed that ARHGDIA that encodes Rho GDP (guanosine diphosphate) dissociation inhibitor α (RhoGDIα, OMIM 601925) was the most likely candidate. Mice with targeted inactivation of ARHGDIA are known to develop severe proteinuria and nephrotic syndrome, therefore this gene was pursued in functional studies. The sisters harbour a homozygous in-frame deletion that is predicted to remove a highly conserved aspartic acid residue within the interface where the protein, RhoGDIα, interacts with the Rho family of small GTPases (c.553_555del(p.Asp185del)). Rho-GTPases are critical regulators of the actin cytoskeleton and when bound to RhoGDIα, they are sequestered in an inactive, cytosolic pool. In the mouse kidney, RhoGDIα was highly expressed in podocytes, a critical cell within the glomerular filtration barrier. When transfected in HEK293T cells, the mutant RhoGDIα was unable to bind to the Rho-GTPases, RhoA, Rac1, and Cdc42, unlike the wild-type construct. When RhoGDIα was knocked down in podocytes, RhoA, Rac1, and Cdc42 were hyperactivated and podocyte motility was impaired. The proband's fibroblasts demonstrated mislocalisation of RhoGDIα to the nucleus, hyperactivation of the three Rho-GTPases, and impaired cell motility, suggesting that the in-frame deletion leads to a loss of function. Conclusions: Mutations in ARHGDIA need to be considered in the aetiology of heritable forms of nephrotic syndrome.